1998
DOI: 10.1021/jf980562q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biophenols on Olive Oil Stability Evaluated by Thermogravimetric Analysis

Abstract: Virgin olive oil stability to autoxidation is mainly due to phenolic compounds naturally occurring in it, but contrasting data have been published on the effectiveness of the same antioxidant compounds. With thermogravimetric analysis (TGA) it is possible to have an estimation of oil resistance to oxidation, having a measure of weight gain percent due to reaction of sample with oxygen during the oxidation, and of initial and final oxidation temperatures. The following samples were examined:  virgin olive oil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 20 publications
3
38
0
1
Order By: Relevance
“…Gennaro et al (1998) and Ali (2008), who reported that the stability of olive oil samples correlated mainly with the total polyphenols content.…”
Section: Results and Discussion: The Physico-chemical Properties Of Vmentioning
confidence: 99%
“…Gennaro et al (1998) and Ali (2008), who reported that the stability of olive oil samples correlated mainly with the total polyphenols content.…”
Section: Results and Discussion: The Physico-chemical Properties Of Vmentioning
confidence: 99%
“…Gennero et al 12 . stated that lipid autoxidation contributes significantly to the deterioration and reduction of the shelf life of many products due to a free-radical chain reaction, and that some of the effects of lipid oxidation are changes in color, texture, odor, and flavor.…”
Section: Resultsmentioning
confidence: 99%
“…polyphenols and tocopherols. The oxidative stability of VOO has been evaluated by several methods: Rancimat test (Di Lecce et al, 2009;Esquivel et al, 2009;Kamvissis et al, 2008;Mateos et al, 2006;Platero-López & García-Mesa, 2007), oxygen stability index (OSI) (Carrasco-Pancorbo et al, 2007;Ceci & Carelli, 2010;Cercaci et al, 2007;Gómez-Caravaca et al, 2007;Márquez-Ruiz et al, 2008), peroxide value (Carrasco-Pancorbo et al, 2007;Di Lecce et al, 2009;Márquez-Ruiz et al, 2008), AOCS method (Diraman, 2008), conjugated dienes (Deiana et al, 2002) and conjugated trienes (Hrncirik & Fritsche, 2005) analyses, K 232 and K 270 UV indexes (Antolin & Meneses, 2000;Cañizares-Macías et al, 2004a;Márquez-Ruiz et al, 2008;Platero-López & García-Mesa, 2007), thermogravimetry analyses (Coni et al, 2004;García Mesa et al, 1993;Gennaro et al, 1998;Santos et al, 2002;Vecchio et al, 2009), differential scanning calorimetry analyses (Vecchio et al, 2009), 13 C NMR on chromatographically enriched oil fractions (Hidalgo et al, 2002), high-resolution chromatographic techniques coupled with UV spectrometry or mass spectrometry (B. Baccouri et al, 2008;Gallina-Toschi et al, 2005;Tena et al, 2009), capillary electrophoresis (Carrasco-Pancorbo et al, 2007;Gallina-Toschi et al, 2005), ultrasound-assisted method (Cañizares-Macías et al, 2004b;Platero-López & García-Mesa, 2007), microwave-assisted method …”
Section: Stability Of Virgin Olive Oilmentioning
confidence: 99%